2012
DOI: 10.5897/sre12.138
|View full text |Cite
|
Sign up to set email alerts
|

A study of the factors affecting construction time in Western Australia

Abstract: Delays are major problems that face the Western Australia's construction industry. Delays can lead to many negative effects such as cost overruns, and is of high concern to those who are involved in the construction industry. This study was set to identify the major causes of delays in the Western Australian construction industry, by means of a literature review and a questionnaire survey. A total of 48 delay factors were obtained from literature review and were further categorised into eight major groups that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Construction projects are usually influenced by overruns. Normative literature has illustrated the frequency and impacts of schedule overruns on stakeholders (Kenny and Vanissorn, 2012;Shebob et al, 2012). Furthermore, studies on overrun factors are prevalent (Kenny and Vanissorn, 2012;Tankkar and Wanjari, 2015).…”
Section: Overrun Causationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Construction projects are usually influenced by overruns. Normative literature has illustrated the frequency and impacts of schedule overruns on stakeholders (Kenny and Vanissorn, 2012;Shebob et al, 2012). Furthermore, studies on overrun factors are prevalent (Kenny and Vanissorn, 2012;Tankkar and Wanjari, 2015).…”
Section: Overrun Causationsmentioning
confidence: 99%
“…Normative literature has illustrated the frequency and impacts of schedule overruns on stakeholders (Kenny and Vanissorn, 2012;Shebob et al, 2012). Furthermore, studies on overrun factors are prevalent (Kenny and Vanissorn, 2012;Tankkar and Wanjari, 2015). Most studies on the subject have used questionnaire surveys, indicating the causations are hard variables (Odeh and Battaineh, 2002;Chan and Kumaraswamy, 1997;Kaliba et al, 2009;Long et al, 2004;Sambasivan and Soon, 2007).…”
Section: Overrun Causationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many existing publications dedicated to causes of profit losses and construction delays on international EPC mega projects: Asia [5][6][7][8][9][10][11][12][13][14][15][16], Europe [17,18], Africa [19][20][21][22], Americas [23][24][25], and Australia [26,27]. Among the factors identified, the most common cause of project schedule and cost overrun was found to be poor design development prior to construction [5][6][7][8]12,13,[15][16][17][18][22][23][24]27].…”
Section: Existing Literaturementioning
confidence: 99%
“…Shrestha [24] studied the magnitude of construction costs and schedule delays based on the type, size, duration and completion years using statistical analysis. Sambasivan [6], Wong [27] and Habibi [23] hypothesized that design error and change is one of the major causes of delays through diverse data analysis techniques, such as a relative importance index ranking method, severe index, etc. Dosumu [22] indicated that about 36% of cost variation is caused by design errors, and recommended design maturity review prior to use to minimize design-error-induced variations.…”
Section: Existing Literaturementioning
confidence: 99%